Analisis Penerapan Nilai-Nilai Keagamaan dalam Pendidikan Anak Usia Dini dan Dampak Psikologi Agama pada Perilaku Harian - Agnesia, Tiara; Munawaroh, Sifa; Sartika, Diah Dwi; Awana, Mardiatun (TSAQOFAH, 2025)
Early childhood education serves as the primary foundation for shaping a child's character and personality holistically, including the internalization of religious values. This article aims to analyze the integration of religious values in early childhood education and the role of Islamic psychology in shaping children's religious behavior. The study employs a descriptive qualitative approach, using literature review and interviews as data collection techniques. The findings indicate that parents and teachers play a central role in instilling religious values from an early age. Moreover, the holistic and tawhid-based approach of Islamic psychology has proven effective in developing the spiritual, emotional, social, and cognitive aspects of children in a balanced manner. This approach not only reinforces moral values and ethics but also provides solutions to the psychological challenges faced by the younger generation in the digital era. A harmonious integration of Islamic education and Islamic psychology enhances the meaningfulness of the learning process and positively contributes to children’s long-term development.